PCR BASED DETECTION OF COAGULASE GENE ENCODING STAPHYLOCOCCUS AUREUS ISOLATED FROM SUBCLINICAL MASTITIS CASES IN BUFFALOES - Malmarugan, S; Arthanarieswaran, M; Suresh, P (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
The present study was carried out to characterize Staphylococcus aureus (S. aureus) isolated from mastitic cases in buffalo based on coagulase gene. A total of 18 strains of S. aureus were isolated during processing of 81 milk samples from 21 buffaloes. The S. aureus strains were characterized phenotypically, and were further characterized genotypically by polymerase chain reaction using oligonucleotide primers that amplified genes encoding coagulase (Coa). Amplification of the Coa gene yielded a product size of 730bp in all 15 coagulase positive isolates. The phenotypic and genotypic findings of the present strategies might provide an understanding of the distribution of the cogulase positive S. aureus clones among buffaloes mastitis isolates, and might aid in the development of steps to control S. aureus infections in buffaloes.
Keywords: Buffaloes; Staphylococcus aureus; sub-clinical mastitis; coagulase gene